A Narrativa documental diegética - CASTRO, Fábio Fonseca de (Pontifícia Universidade Católica do Rio Grande do Sul, 2022)
The article discusses the ethos of interpretive action in carrying out ethnographic film and, from it, the nature of work with images in social research. Understanding this interpretive action as a diegetic process, it seeks to reflect on the validity of the interpretive method, on the political relationship this method has with reality and with its own effectiveness. In general, the article oposes diegetic narrative to the dialetic one. The first one plays a hermeneutic, or better, understanding and interpretive narrative pattern. The second, meanwhile, is focused on the requirement of an epistemological surveillance of the image, a requirement of the order of description, necessarily objectivist.